2020
DOI: 10.14814/phy2.14648
|View full text |Cite
|
Sign up to set email alerts
|

Spinal spatial integration of nociception and its functional role assessed via the nociceptive withdrawal reflex and psychophysical measures in healthy humans

Abstract: Many pain-related conditions are characterized by poorly localized pain areas in the body which is likely to reflect abnormal processing of spatial characteristics of the noxious phenomenon driving the condition (Gran, 2003; Graven-Nielsen & Arendt-Nielsen, 2010; Kamaleri et al., 2008; Wolfe et al., 1990). Within the spinal cord, several primary afferents converge onto spinal neurons and constitute the first relay for somatosensory integration. Electrophysiological studies in animals have shown that neurons lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 79 publications
5
9
0
Order By: Relevance
“…Animal studies confirmed that spinal neuronal networks indeed encode spatial characteristics of the stimulus to elaborate a reflex response [148]. Similarly, the results of Study I [1] seem to indicate that spinal nociceptive processing integrates spatial information of the stimulus to elaborate the optimal reflex response in healthy humans. Whether that information is preserved through the whole integrative process, and whether it becomes available to the human subjective experience of pain, remains elusive to clarify.…”
Section: Spinal Spatial Integration Of Nociceptionsupporting
confidence: 53%
See 4 more Smart Citations
“…Animal studies confirmed that spinal neuronal networks indeed encode spatial characteristics of the stimulus to elaborate a reflex response [148]. Similarly, the results of Study I [1] seem to indicate that spinal nociceptive processing integrates spatial information of the stimulus to elaborate the optimal reflex response in healthy humans. Whether that information is preserved through the whole integrative process, and whether it becomes available to the human subjective experience of pain, remains elusive to clarify.…”
Section: Spinal Spatial Integration Of Nociceptionsupporting
confidence: 53%
“…Evidence of spatial summation assessed via the NWR in healthy humans is scarce. Study I [1]showed that paired stimulation elicits significantly larger NWR than single stimulation. The magnitude of the NWR increased 73% when the area of stimulation doubled in size, suggesting SS in the NWR pathway.…”
Section: Spinal Spatial Integration Of Nociceptionmentioning
confidence: 95%
See 3 more Smart Citations